1994
DOI: 10.1093/geront/34.2.190
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Care Service Use by Frail Elders: Is Ethnicity a Factor?

Abstract: Using data from the 1982-84 National Long-Term Care Channeling Demonstration, this study examines factors associated with long-term care service use by African American, Hispanic, and white frail elders living in the community. Findings indicate that in addition to predisposing, enabling, and need factors, race/ethnicity is a significant predictor of each type of service use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(89 citation statements)
references
References 0 publications
5
82
2
Order By: Relevance
“…Consistent with the theory of reasoned action (Ajzen and Fishbein 1980), the relationship between attitudes and intention is positive and strong in the context of long-term care arrangement (Mui and Burnette 1994;Rabiner 1996;Schoenberg and Coward 1997).Among the three age cohorts, intention toward old age home placement increases with more positive attitudes toward old age homes.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Consistent with the theory of reasoned action (Ajzen and Fishbein 1980), the relationship between attitudes and intention is positive and strong in the context of long-term care arrangement (Mui and Burnette 1994;Rabiner 1996;Schoenberg and Coward 1997).Among the three age cohorts, intention toward old age home placement increases with more positive attitudes toward old age homes.…”
Section: Discussionsupporting
confidence: 55%
“…Consistently, previous studies have shown that positive attitudes toward old age homes increase the odds of subsequent utilization of old age home services (Rabiner 1996;Schoenberg and Coward 1997). In addition, they are even stronger indicators than cognitive and daily activity impairments of older people (Mui and Burnette 1994). Negative attitudes toward old age homes, such as the perception that they are places where older people go to die, are related to older people's resistance to long-term placement in them (Lee 1997;Liu and Tinker 2001;Sandell et al 1993;Schoenberg and Coward 1997).…”
Section: General Psychological Factors Associated With Old Age Home Pmentioning
confidence: 99%
“…Early studies using data from pre-Balanced Budget Act (BBA) periods found contradictory results in terms of use of home health care services. Some studies have found differences in use by race, for example, with African Americans less likely to use in-home services than Whites (Kemper, 1992;Mui & Burnette, 1994). Others found that African Americans were more likely to use formal services than whites (Bass & Noelker, 1987;Kemper, 1992;White-Means & Rubin, 2004).…”
Section: Health Disparitymentioning
confidence: 99%
“…Most previous studies examining predictors of formal service use by older adults use the Anderson-Newman Behavioral Model (Burnette & Mui, 1995;Calsyn & Roades, 1993;Mitchell et al, 1997;Mui & Burnette, 1994). Despite the volume of such studies, predictor results are inconclusive.…”
Section: Literature Review On Service Usementioning
confidence: 99%